2012
DOI: 10.2754/avb201281010037
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of broiler carcasses during slaughter processing

Abstract: Microbial contamination of poultry carcasses can be influenced by many factors during transport and slaughtering. The aim of this study was to evaluate the impact of four processing steps (plucking, evisceration, washing and chilling) on the total viable counts (TVC), counts of Escherichia coli, Salmonella spp. and Listeria spp. incidence on broiler carcasses. A total of 160 broiler carcasses originating from one farm were collected during one year period at a Czech slaughterhouse and examined. Both TVC and E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
3
17
1
Order By: Relevance
“…Svobodov et al [8] obtained similar results when they counted bacteria in broiler carcasses during the several stages in the industrial process, and contamination by E.coli was verified in decreased with each subsequent stage during the industrial process. Alvarez et al [16] quantified E. coli in chicken cuts bought in shops in León, Spain, and obtained averages between 2.6 and 4.3 log CFU.g -1 , higher than those reported in current assay.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Svobodov et al [8] obtained similar results when they counted bacteria in broiler carcasses during the several stages in the industrial process, and contamination by E.coli was verified in decreased with each subsequent stage during the industrial process. Alvarez et al [16] quantified E. coli in chicken cuts bought in shops in León, Spain, and obtained averages between 2.6 and 4.3 log CFU.g -1 , higher than those reported in current assay.…”
Section: Discussionsupporting
confidence: 57%
“…Svobodová et al [8] assessed chicken carcasses during the processing stages in an abattoir in the Czech Republic and isolated 14 Listeria spp. strains in 12 carcasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 14 studies investigating this stage (Barbut et al, 2009;Berrang & Dickens, 2000;Cox et al, 2010;Fluckey et al, 2003;Gill et al, 2006;Matias et al, 2010;Oyarzabal et al, 2004;Stopforth et al, 2007;Svobodova et al, 2012;Vaidya et al, 2005;Whyte, McGill, Monahan, & Collins, 2004), 11 described a statistically significant reduction. Both the overall effect size as well as the confidence interval described a positive effect of chilling stage on counts reduction.…”
Section: Meta-analysis Of Studies Reporting Data For E Colimentioning
confidence: 90%
“…Fourteen studies investigated reduction attributable to the washing step; eleven studies showed a decrease of E. coli counts after this operation (Barbut et al, 2009;Berrang & Dickens, 2000;Kemp, Aldrich, Guerra, & Schneider, 2001;Matias et al, 2010;Northcutt, Berrang, Smith, & Jones, 2003;Oyarzabal, Hawk, Bilgili, Warf, & Kemp, 2004;Stopforth et al, 2007;Svobodova, Borilova, Hulankova, & Steinhauserova, 2012;Vaidya et al, 2005), while three studies (Barbut et al, 2009;Oyarzabal et al, 2004;Stopforth et al, 2007) recorded a very small increase of the counts. From a statistical point of view, washing was effective in reducing bacterial counts; however, it failed to reach practical significance against our threshold value (Details in Fig.…”
Section: Meta-analysis Of Studies Reporting Data For E Colimentioning
confidence: 97%